Assessment of PM-EDM cycle factors influence on machining responses and surface properties of biomaterials: A comprehensive review - Al-Amin, M. (Elsevier Inc., 2020)
Powder mixed-electro discharge machining (PM-EDM) is recently evolving machining technique which can simultaneously remove and modify the machined surface through thermo-electrical process. It is a modified form of EDM in which the conductive powder elements are added in the dielectric liquid to enhance machined surface characteristics and machining responses. The commonly used biomaterials such as 316L stainless steel, Ti-based alloy, NiâTi, Mg alloy, and CoâMoâCr alloy have excellent mechanical characteristics while the biofunction of these materials are not in satisfactory level. Due to higher hardness, brittleness, and heat resistant natures of the biomaterials, it is very challenging to machine them with conventional machining. Both the system efficiency and modified surface properties depend on the associated electrical and non-electrical factors of PM-EDM cycle. This review focuses on the influence of process factors such as current, pulse duration, tool-polarity, duty cycle, potential voltage, types of liquid, and added powder concentration on performance outputs including material removal and tool wear rate, coating thickness, coarseness, microhardness, coating adhesion bonding, biocompatibility, and resistant to corrosion. This study also discusses influence of various powders on machining and modified surface characteristics of biomaterials. The future research scopes and challenges of PM-EDM process are included in this study thoroughly. Â© 2020 Elsevier Inc.